Cognitive and Behavioral Changes in Patients Treated With Droxidopa for Neurogenic Orthostatic Hypotension: A Retrospective Review - McDonell, Katherine E (Cogn Behav Neurol, 2019)
BACKGROUND: Droxidopa is a norepinephrine precursor that improves symptoms of neurogenic orthostatic hypotension in conditions such as Parkinson disease, multiple system atrophy, and pure autonomic failure by inducing a pressor effect. Unlike other pressor agents, droxidopa crosses the blood-brain barrier; however, its central effects are, as of yet, uncharacterized. OBJECTIVE: We present the results of a retrospective cohort study examining cognitive and behavioral side effects linked to droxidopa therapy. METHODS: We performed a review of 101 patients who had been treated with droxidopa at an academic tertiary care center and identified cases of cognitive and behavioral changes associated with the therapy. RESULTS: We identified six patients who had developed cognitive and behavioral symptoms, including memory difficulties, confusion, mania, and irritability, shortly after droxidopa initiation. All six patients displayed symptoms of synucleinopathy, manifesting with autonomic failure, rapid eye movement sleep behavior disorder, and parkinsonism. Patients had no significant cognitive or behavioral symptoms before droxidopa initiation. Behavioral disturbances were observed early in the droxidopa titration period and at relatively low doses. Symptoms resolved with dose reduction in four patients, and droxidopa was discontinued in two patients due to persistent irritability. No other medical comorbidities or alternative etiologies were identified to explain the symptoms. CONCLUSIONS: Droxidopa is designed to act peripherally as a pressor agent but may also exert important central effects. We hypothesize that the cognitive and behavioral manifestations observed in the patients with orthostatic hypotension resulted from an “overdose” of key noradrenergic networks linking orbitofrontal and mesolimbic regions.